Keys to the global treeline formation: Thermal limit for its position and moisture for the taxon-specific variation - Yuyang Xie; Zehao Shen; J. Julio Camarero; Josep Peñuelas; Xuejing Wang; Jitang Li; Wenge Rao; Xiangwu Chen; Fu Zhao; Xiao Feng (Proceedings of the National Academy of Sciences, 2025)
Alpine treeline is a prominent biogeographic feature worldwide, determined by the physiological limit of tree life form. There are considerable variations in the various dimensions of physiological limit among tree taxa; thus, varied environmental drivers and spatial patterns are expected for different tree taxa at treelines. However, such taxonomic variability of treeline is often overlooked in large-scale studies. Here, we assembled, to our knowledge, the most comprehensive dataset of tree species at alpine treelines, drawing from research conducted over the past half-century, encompassing over 2,000 records across 38 mountain regions and 43 countries. Using this extensive global dataset, we examined the spatial patterns and environmental drivers shaping different tree taxa at treelines worldwide. The highest tree richness at treelines was found in mid-latitude mountains of the Northern Hemisphere, reflecting floristic differentiation caused by continental isolation. Moisture and climatic variability, particularly seasonal fluctuations, determine the turnover of tree taxa at treelines. Heat limitations appear to restrict the establishment of all genera, effectively defining treeline positions. Heat conditions at treeline positions tend to be about 35% below the genus- and species- level thermal optima. This thermal threshold can effectively explain the global pattern of uppermost tree elevation. Our findings highlight the synergic effects between heat and moisture in determining the taxonomic variation in treeline formation, offering insights for alpine treeline studies under climate change.